LE CARTE DI ACCOMPAGNO: RICOSTRUIRE I RETROSCENA DELLE FOTOGRAFIE AEREE - Maria Modaffieri (GEOmedia)
The article describes the detailed process of managing aerial photographs during World War II, preserved in the Aerofototeca Nazionale in Rome. The individual frames resulting from Allied reconnaissance missions were accompanied by index maps containing crucial information for image analysis and interpretation. After each flight, the film was developed, and the pilot traced a detailed itinerary (pilot trace) to document the covered targets and encountered conditions. The Interrogation Report, another highly important document, provided essential information about the flight and its objectives, such as cloud cover or the discovery of enemy aircraft. The photographs were carefully titled and recorded to ensure accurate interpretation. Moreover, prints had to be produced quickly and duplicated before being sent to headquarters. The aerial imagery management system, which included the use of continuous printers, was crucial to the success of Allied military operations.